Comparison of volume-controlled, pressure-controlled, and chest compression-induced ventilation during cardiopulmonary resuscitation with an automated mechanical chest compression device: A randomized clinical pilot study. (September 2021) - Fuest, Kristina; Dorfhuber, Florian; Lorenz, Marco; von Dincklage, Falk; Mörgeli, Rudolf; Kuhn, Karl Friedrich; Jungwirth, Bettina; Kanz, Karl-Georg; Blobner, Manfred; Schaller, Stefan J
Abstract: Aim of the study: Automated mechanical chest compression devices (AMCCDs) can help performing high-quality cardiopulmonary resuscitation (CPR). Guidelines for CPR are lacking information about the optimal ventilation mode during CPR using AMCCDs. Aim of this pilot study was to compare three common ventilation modes during CPR using AMCCD. Methods: In this randomized controlled trial, we included patients with an out-of-hospital cardiac arrest arriving at the resuscitation room receiving chest compressions via AMCCD with an expected continuation of at least 15 min. Patients were randomly assigned to three groups: biphasic positive airway pressure with assisted spontaneous ventilation (BIPAP) with assisted spontaneous breathing, continuous positive airway pressure (CPAP) and volume-controlled ventilation (VCV). Outcomes were tidal volume, respiratory minute volume, and end-tidal CO2 during the study period. Groups were compared using generalized linear models. Data is given as median and interquartile ranges. Results: Of 53 screened patients, 30 were randomized. The tidal volume was significantly (p < 0.05) lower in patients of the CPAP group (68 [64–83] ml) compared with those of the BIPAP (349 [137–500] ml), while the respiratory minute volume differed between the CPAP group (6.2 [5.3–8.1] l/min) and both the BIPAP (7.1 [6.7–10.2] l/min) and VCV group (7.2 [3.7–8.4] l/min). Conclusions: All ventilation modes achieved an adequate respiratory minute volume during CPR with an AMCCD. However, BIPAP seems to be superior due to the higher tidal volume. Therefore, we recommend starting mechanical ventilation when using AMCCD with BIPAP ventilation to avoid risks related to dead space ventilation.